Vernetztes Leben. Soziale und digitale Kulturen - Robertson-von Trotha, Caroline Y. (Problemkreise der angewandten Kulturwissenschaft / ZAK, Zentrum für Angewandte Kulturwissenschaft und Studium Generale, 2006)
The Internet has taken with its unlimited communication structures an outstanding role. In the process of globalization this creates not only the possibility for the integration of access to information independent from time and place, it also implies social changes with not yet known consequences. How is our society changing under these new communication structures? Is the "networked egoist" putting an end to the collective responsibility and to the sense of community? Or does networking provide the opportunities for the future development of civil societies, democracy, tolerance and peace?